Evaluation of Average Directional Effective Emissivities of Isothermal Cylindrical-inner-cone Cavitties Using Monte-Carlo Method - Nguyen Quang, Minh; Nguyen Van, Binh (Communications in Physics, 2017)
We have used the Monte Carlo method based on theory of successive reflections and ray tracing to calculate the average normal directional effective emissivities of isothermal cylindrical-inner-cone cavities for various geometrical parameters. A simplified specular-directional diffuse reflection model was applied in our calculations for cavities working in the infrared spectral range. Our results are in good agreement comparing with what obtained by other authors. The algorithm developed by us has an advantage in simplicity and time saving of calculations. It can be used in blackbody cavity design considerations, especially in the cylindrical-inner-cone cases.